Optimal coordinated generator tripping and load shedding for power system stability enhancement - Zhu, Yang (Nanyang Technological University, 2023)
With the rapid development of society, power system has become more complex and faces significant challenges to safety and stability. This dissertation focuses on the transient stability problem and proposes an optimal coordinated emergency control (EC) strategy for stability enhancement. Emergency control actions such as generator tripping or load shedding have been widely applied to maintain transient stability, but few works investigate their coordination. The proposed strategy aims to implement generator tripping and load shedding simultaneously, and the objective is to minimize total control costs while maintaining system stability. This dissertation applied an open-source python-based tool called ANDES [15] to run the Time Domain Simulation (TDS). EEAC is used to conduct Transient Stability Assessment (TSA), and trajectory sensitivity analysis is applied to linearize transient stability constraint. The Gurobipy [27] is applied to solve the optimization problem. The optimal control solutions for generator tripping and load shedding can be obtained, and the effectiveness of the coordinated control method is verified in the New England system [25]. Compared with single-control actions, the proposed method is more efficient and economical.